2022
DOI: 10.3390/healthcare10122485
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Care on HIV/AIDS-Positive Men Who Have Sex with Men: A Qualitative Descriptive Study of Nurse’s Perspective in Indonesia

Abstract: HIV/AIDS-positive men who have had sex with men (MSM) account for roughly one-third of new infections in the region, with numerous nations facing a high and rising prevalence. They often face stigmatization and discrimination from society, including nurses. This study aims to explore nurses’ perspectives on caring for HIV/AIDS-infected MSM. A descriptive qualitative design was utilized. Fifteen nurses who cared for HIV/AIDS-positive MSM in the two hospitals in Jakarta, Indonesia, were recruited with purposive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This can support their ability when dealing with patients. (See quotes [7][8] Improvement of communication skills and the need for a communication guide Then another ability increase that is no less important according to the participants is an increase in their communication when dealing with patients and they need communication standard guidelines in dealing with patients, so they have guidelines. (See quotes 9-10)…”
Section: Theme 2: Need To Increasing Skills and Knowledge Of Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can support their ability when dealing with patients. (See quotes [7][8] Improvement of communication skills and the need for a communication guide Then another ability increase that is no less important according to the participants is an increase in their communication when dealing with patients and they need communication standard guidelines in dealing with patients, so they have guidelines. (See quotes 9-10)…”
Section: Theme 2: Need To Increasing Skills and Knowledge Of Nursesmentioning
confidence: 99%
“…A qualitative study about nurses’ perspectives on caring for HIV-positive MSM showed negative nurse perceptions in the early phase of treatment, nurse attitudes contrasting with negative perceptions, and nurses with knowledge of HIV. 8 Furthermore, it has been discovered that negative perceptions from nurses only appear during the initial phase of treatment, followed by a positive attitude. After interacting with patients and receiving HIV training, nurses appear to have a better understanding of caring for HIV-positive individuals.…”
Section: Introductionmentioning
confidence: 99%